Implementasi Pengembangan Keprofesian Berkelanjutan Bagi Guru-Guru Bersertifikasi Pendidik Di SMK Bhinneka Karya Simo-Boyolali - Jumali, Jumali, Prof. Dr. Bambang Sumardjoko, M.Pd, Dr.Sabar Narimo, M.M., M.Pd (2016)
The aims of these research are to describe characteristics of: (1) Continuing professional development program for teachers certified educators for teachers at SMK Bhinneka Karya Simo, (2) Implementation of continuing professional development for teachers certified educators in SMK Bhinneka Karya Simo. This research is deskriftif qualitative design case study of a process and the implementation of policies on the implementation of professional development of continuing data collection method interview, observation and documentation. This research validity of the data using a triangulation of data by combining interviews, documentation and observation. Data analysis techniques include: data collection, data presentation, data reduction, and conclusion or verification. Programming and implementation of activities of continuing professional development of teacher at SMK Bhinneka Karya Simo with activities, namely: (1) Self-development through education and training of teachers is reflected in the learning, (2) Scientific publication with drafting teaching materials or modules, and the development of research in education, (3) The innovative work with the activity of making props as well as establishing guidelines for the exam and test results in the form of lattice exam or a test. Continuing professional development is expected to have an impact on improving the competence of teachers which impact on the quality of students' good results and the learning process. Principal in the implementation of continuing professional development has a strategic headmaster as a supervisor, as a motivator and as an evaluator. Keywords: continuing professional development.